Examining the mediating function of SIRI in the association between LC9 and chronic obstructive pulmonary disease - Wang, Ziming; Xie, Xinyun; Gong, Hongyang (Frontiers in Medicine, 2025)
BackgroundChronic obstructive pulmonary disease (COPD) is a major contributor to early mortality, high overall mortality rates, and significant healthcare costs. Based on the Life’s Essential 8 (LE8), Life’s Crucial 9 (LC9) is a new cardiovascular health evaluation instrument that also includes a mental health examination, while the systemic inflammation response index (SIRI) is an emerging biomarker of systemic inflammation. The purpose of this study is to look at the link between LC9 and COPD and how SIRI may play a mediating function in it.MethodsData from 25,721 U.S. participants in the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018 were used in a cross-sectional study. To investigate the relationship between COPD and LC9, multivariable logistic regression, restricted cubic splines (RCS), and subgroup analysis were used. Furthermore, a mediation study was conducted to evaluate SIRI’s possible involvement in the connection between LC9 and COPD.ResultsIt consisted of 25,721 persons in all, 1,257 of whom had COPD. When multiple covariates were taken into account, logistic regression analysis showed that a 28% decrease in the prevalence of COPD was linked to every 10-point increase in LC9 (OR = 0.72, 95% CI: 0.67, 0.77), while a 1.17-fold increase in the prevalence of COPD was linked to each unit increase in SIRI (OR = 1.17, 95% CI: 1.10, 1.25). When LC9 and SIRI were divided into tertiles, similarities were seen (P for trend <0.001). A linear negative correlation between LC9 and the prevalence of COPD was shown using RCS analysis. Also, mediation analysis indicated that SIRI mediated 1.64% of the link between LC9 and COPD (p < 0.001).ConclusionAs shown by this study, LC9 and COPD display a substantial negative connection, which is largely mediated by SIRI. These results demand more investigation because they show a possible connection between cardiovascular health and COPD and offer fresh perspectives on the role systemic inflammation plays in this relationship.